PENGARUH ONLINE CUSTOMER RATING DAN ONLINE CUSTOMER REVIEW TERHADAP KEPUTUSAN PEMBELIAN PRODUK FASHION PADA PENGGUNA MARKETPLACE TIKTOK SHOP TANGERANG TAHUN 2024 - Majid, Amalia Sandya; Yasaningthias, Ghita (JAMBIS : Jurnal Administrasi Bisnis, 2024)
This study aims to analyze how much influence online customer ratings and online customer reviews have on purchasing decisions for fashion products at the TikTok Shop Tangerang marketplace. This study uses quantitative research methods with explanatory research types. The population in this study consisted of TikTok Shop marketplace users. The sample used was 120 respondents with Non-Probability Sampling  sampling  technique  with  Accidental  Sampling  approach.  The  data  analysis methods  used  in  this  study  are  instrument  test,  classical  assumption  test,  hypothesis testing  and  multiple  linear  regression  test.  The  results  showed  that  online  customer rating  has  a  positive  and  significant  effect  on  purchasing  decisions  with  a  percentage of  84.6%.  Online  customer  review  has  a  positive  and  significant  effect  on  purchasing decisions with a percentage of 88.2%. The amount of  online customer rating and online customer  review  on  purchasing  decisions  with  a  percentage  of  89.6%.